The difficulty to diagnose cervical cancer developing in the perinatal period with the first‐trimester cytology: A retrospective study. Issue 9 (9th June 2021) - Yamazaki, Hiroyuki; Mitamura, Takashi; Ihira, Kei; Endo, Daisuke; Sakurai, Manami; Konno, Yosuke; Watari, Hidemichi
Abstract: Aim: Cytological cervical cancer screening for pregnant women is routinely performed and still plays an essential role in Japan because of the considerably low rate of human pappillomavirus (HPV) vaccination. Though almost all pregnant women undergo cytological screening at their first trimester, we experienced invasive cervical cancers (ICC) diagnosed during pregnancy or postpartum period. We investigated the characteristics of perinatally diagnosed ICCs to clarify the difficulty in diagnosis during the pregnancy. Methods: We retrospectively reviewed the clinical data on ICC diagnosed during pregnancy or within 1 year after delivery from 2010 to 2018 at Hokkaido University Hospital. Results: We identified 18 ICC patients, and the median follow‐up period was 46.5 months. Among eight patients with negative for intraepithelial lesion or malignancy (NILM), the mean duration to reach ICC diagnosis was 10.7 months, seven had stage IB1 or worse, and one was dead. On the other hand, among 10 women with abnormal cytology, the mean duration for diagnosis was 1.4 months, and 6 had stage IB1 or worse, and 1was dead. In terms of the timing of the final diagnosis, 8 were during pregnancy and 10 in the postpartum periods. Among eight pregnant patients, three resulted in a preterm delivery (33, 34, and 35 gestational weeks), and four terminated their pregnancies. One decided to continue the pregnancy until the term period. We performed conization in one patient and hysterectomy in seven. Conclusion: A part of cytological examinations of pregnant women may result in presumed false‐negative or underestimation, which keeps them away from the additional examination to find ICC.